Immediate local flap versus skin graft reconstruction after standard excision of basal cell carcinoma of the nose - Tuukka Veija; Veerakaisa Koivunen; Lotta Mäkelä; Virve Koljonen (JPRAS Open)
Summary: Basal cell carcinoma (BCC) of the nose requires surgical excision and often reconstruction with a local flap or a skin graft. Although standard excision remains common, the international guidelines lack consensus on whether the reconstruction should be performed after the histological margins are confirmed. In this retrospective study, we analyzed all consecutive cases of nasal BCC operated in the Hospital district of Helsinki and Uusimaa in 2015-2016 using standard excision and immediate reconstruction. The characteristics of the patients’ and tumors were compared with the reconstruction method used: linear closure, local flap, or skin graft. Especially, the risk factors for re-excision were investigated. Overall, 305 patients and 318 BCCs were included in the study. Among them, 112 (35.2%) cases were reconstructed with local flaps, 66 (20.8%) with skin grafts, and 140 (44.0%) via linear closure. Flap reconstruction was common for alar and flank defects while tip defects were often skin grafted. For defects of the base and dorsum, there were no clear favorites. In 25 cases (7.9%), the re-excision was carried out due to margin involvement. There was no difference in the risk for re-excision between the different reconstruction groups. Tumor recurrence during the median follow-up time of 7.5 half years was only 3.8%. We did not identify any clear risk factors for re-excision or recurrence. Notably, neither the aggressive subtype nor subunit location were associated with the risk of re-excision. We suggest that standard excision of BCC of the nose and immediate reconstruction is a reasonable treatment option.